PTH-125 Survival Following Intestinal And Multivisceral Transplantation At Addenbrooke's Hospital, Cambridge, Uk. (9th June 2014) - Rutter, C; Sharkey, L; Butler, A; Russell, N; Pither, C; Green, J; Duncan, S; Bond, D; Chukualim, B; Woodward, J; Gabe, S; Jamieson, N; et al.
Abstract : Introduction: Small intestinal transplantation (SBT) was first undertaken in the UK in Cambridge in 1991. Since the introduction of new immunosuppressive agents around the millenium, results have improved and we present our experience over the last 10 years. Since 2003, 47 tranplants have been performed on 43 patients. Grafts include small bowel or small bowel/colon (SBT), liver and small bowel (LSBT), modified multivisceral (MMVT – small bowel, stomach, pancreas, no liver) and multivisceral (MVT – intestine, stomach, pancreas and liver) transplantation. Cambridge is the only UK centre offering MVT in adults. Methods: A review of all patients who underwent small intestine and multivsiceral transplantation at Addenbrooke's Hospital between 2003 and 2013. Kaplan-Meier survival data are shown for each group of organs transplanted. Results: Five year survival for all patients transplanted is 77%. Survival curves for each organ group transplanted is graphed below: Conclusion: Five year survival in our patients transplanted since 2003 is 100% for SBT and LSBT and 65% for MVT, compared with international registry survival figures of 59% (SBT and LSBT combined) and 22% respectively. In recent years we have also experienced an increase in the number of urgent transplants performed and these patients are often critically unwell at the time of surgery. Our centre undertakes a relatively large number of procedures and this, coupled with a particular focus on multidisciplinary team working, may account in part for our favourable survival figures. Disclosure of Interest: None Declared.